Development for an equitable society - Nasir, Jamil (Pakistan Jumhoori publications, 2020)
This book explained how the Pakistan economics evolved as a paradigm society. Furthermore, it examines some of the economic elements that drive economic trade and development in modern society.
asm, 21/04/21
Loans
Keywords: economics development; development economics; economic policy; social policy; Pakistan